Temperature Dependence of Water Crossover in Proton Exchange Membrane Water Electrolysis - Friedrichs-Schucht, Maurice; Hasché, Frédéric; Oezaslan, Mehtap (ECS transactions, 2023)
In this work, we investigated the temperature dependence on the water transport coefficient for proton exchange membrane water electrolysis (PEMWE). The experimental parameters varied between 40 and 80 °C at a current density of 1 A cm -2 geo and ambient pressure. The water crossover to the cathode was measured by cooling the exhaust and weighing the liquid fraction over 4 hours under steady conditions. The remaining water vapor from the gaseous fraction was taken into account by the temperature-dependent vapor pressure curve. The resulting data of the water crossover [mg cm -2 geo min -1 ] depends on the temperature, time and current density applied. The main driving force of the water crossover is the proton flux through the membrane and can be established by fitting the data of the relative changes in water mass over time with a linear function. For now, the water diffusion which has a minor contribution is not considered. Our results reveal that the water transport coefficient derived from the proton flux increases from 2.4 at 40 °C to 3.1 at 80 °C (growth of +29%). In summary, we have developed a method to more accurately determine the water transport coefficient, which is very useful in modeling the water crossover in PEMWE.